Grape Dryer Using Infrared Radiation : An Experimental Study - Santosh, Joshi Snehal; Vishnu, Joshi Santosh (Journal of Food Science and Technology Nepal, 2014)
Preserving fruits by drying is an important operation continued from prehistoric period. Infrared radiation can be used for grape drying purpose. It is unique process and distinctly different from conventional or natural drying. The infrared radiations accelerate drying process with a better control to achieve uniform drying, reduced drying time and ultimately improved product quality. Besides, it requires less floor space and compact system are the additional advantages. In this paper existing natural grape drying process is modified with suitable enclosure containing IR radiators and allied system. Appropriate sensors are used to measure parameters like humidity, temperature and weight of sample. Experimental analysis done with the help of dryer proves the uniform drying of the grapes with the help of infrared radiation. The original color of grapes is better conserved as the drying takes place at low temperature. The drying time is reduced to a significant level as compared to natural drying process. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11722 J. Food Sci. Technol. Nepal, Vol. 8 (18-22), 2013